Assessment the Immunohistochemical Expression of Cathepsin D in Iraqi Patients with Colorectal Carcinoma - Mohamad, Ban; Zghair, Khawla; Zghair, Faeza; Mohammed, Reyadh (Iraqi Journal of Science, 2025)
In the current study hundred ten of Iraqi patients with colorectal tumors were studied to evaluate the expression of Cathepsin D using Tissue microarray-Immunohistochemisty (TMA-IHC) technique. Of them, Ninety cases had colorectal carcinoma, and twenty had benign tumors. A group of twenty cases of non-specific colitis and other twenty colonic biopsies without significant pathology were also studied. Results revealed high expression of Cathepsin D in tumors (96.7% of malignant cases, 80% of adenomas) versus 30% of colitis. As well high significant differences (P< 0.001) in the expression of CathepsinD in different tumor types (adenocarcinoma and mucinous carcinoma), tumor stages and grades.